Efeitos de instruções e história experimental sobre a trnsmissão de práticas de escolha em microculturas de laboratório - LEITE, Felipe Lustosa (Universidade Federal do Pará, 2014)
The selection of cultural practices has been a subject matter of increasing object of interest in Behavior Analysis, majorly after the formulation of the concept of metacontingency by S. S. Glenn. One of the themes approached has been the relation between rule-governed behavior and the transmission of cultural practices. The present study had the objective of evaluating the effects of verbal instructions on the transmission of a choice practice in small groups. Forty-three undergraduate students participated in the study, divided into four groups. The participants, in groups of three, had to collectively solve a problem in a condition which could lead to two possible gains: one more advantageous in the long term (choice of black lines) and another one less advantageous (choice of white lines). At each 12 minutes one participant would leave the group and a new one would be introduced in it, being the responsibility of the older participants to teach the new one on how to proceed in the task. In some groups, participants called confederates were instructed to teach the task wrongly, inducing the group to choose white lines, leading to less a advantageous result. The confederates instructed the participants with two categories of instructions: false descriptive and prescriptive. With the participant change cycle, the confederates gave place to naïve or experienced participants. The results indicate that when confederates took part in groups constituted by naïve participants, the choices less advantageous for the group were predominant, in which Group 2 maintained the choice pattern instructed by the confederates for one additional generation and Group 4 maintained it for two additional generations. When the confederates took part in groups with participants previously exposed to the task (Groups 1 and 3), both groups returned to choices according to the pattern established in a baseline session (approximately 80% of black choices for Group 1 and 60% for Group 3). As for the type of instruction employed by the confederates, when participants were instructed with false descriptive instructions the choice pattern instructed by the confederates was maintained for fewer generations than when they were instructed with prescriptive instructions. It is concluded that a previous experience to a task can enable the group to suffer less effects of verbal manipulation which lead to a less advantageous choice practice and that instructions which do not describe contingency relations between events are less effective to verbally control choice practices.